2019
DOI: 10.2131/fts.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine supplementation modulates oxidative stress by inhibiting hepatic adenosine diphosphate (ADP)-ribosylation in obese diabetic rats

Abstract: Diabetic hyperglycemia is typically accompanied by various protein modifications, indicating hyperglycemic glucotoxicity. Overactivation of poly [adenosine diphosphate (ADP)-ribose] polymerase 1 (PARP-1) has been implicated in the pathogenesis of oxidative stress-related diseases including diabetes and its complications. Furthermore, obesity and diabetes are known to be associated with a substantial risk of chronic liver disease. We have previously reported that thiamine supplementation prevented obesity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…We recently determined the beneficial effect of longterm consumption of thiamine water in obese diabetic rats (Kohda et al, 2012(Kohda et al, , 2017Tanaka et al, 2010). Daily consumption of water containing thiamine may enable modulation of oxidative stress-related diseases, such as diabetes and its complications (Kohda et al, 2019). In this study, after consuming thiamine in drinking water for 28 weeks, body weight gain and high blood pressure were significantly ameliorated in obese diabetic rats.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We recently determined the beneficial effect of longterm consumption of thiamine water in obese diabetic rats (Kohda et al, 2012(Kohda et al, , 2017Tanaka et al, 2010). Daily consumption of water containing thiamine may enable modulation of oxidative stress-related diseases, such as diabetes and its complications (Kohda et al, 2019). In this study, after consuming thiamine in drinking water for 28 weeks, body weight gain and high blood pressure were significantly ameliorated in obese diabetic rats.…”
Section: Discussionmentioning
confidence: 62%
“…We recently established that long-term consumption of thiamine water by obese diabetic rats leads to reduced obesity and metabolic disorders (Tanaka et al, 2010;Kohda et al, 2012Kohda et al, , 2017. In addition, we found that drinking thiamine water daily may modulate oxidative stress-related diseases, such as diabetes and its complications (Kohda et al, 2019). Orexin-A has been suggested to control hypertension, feeding behavior, and obesity (Sakurai et al, 1998;Shirasaka et al, 1999;Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 77%
“…Vitamin is a water-soluble vitamin [8] containing amino and sulfur elements, so it is also known as thiamine. What we can buy on the market is usually thiamine hydrochloride or nitrate [9]. V has an important nutritional and health care function in our body, which participates in the important link of carbohydrate metabolism and heat metabolism in our body, so V demand is calculated according to the proportion of individual body heat consumption.…”
Section: Vitaminmentioning
confidence: 99%